Feasibility of skin-friction diagnostics based on surface pressure gradient field. (28th October 2016) - Liu, Tianshu; Misaka, Takashi; Asai, Keisuke; Obayashi, Shigeru; Wu, Jie-Zhi
Abstract: An intrinsic relation is given between the skin-friction vector and the surface pressure gradient through the boundary enstrophy flux (BEF), and it is used to study the possibility to extract some skin-friction structures from a surface pressure field. This attempt contains two related parts. In the first part, when the BEF field is given, a projected skin-friction field in the image plane can be sought from a surface pressure image based on a variational solution of an optical-flow-like equation. This approach is validated in several classical flows. The second part deals with a practical problem in which the BEF field is not known a priori . In this case, a so-called auxiliary skin-friction field is determined from a surface pressure image alone by using the same variational approach. The auxiliary skin-friction field has the magnitude proportional to the skin-friction magnitude and the direction of the negative surface pressure gradient. The physical meaning of the auxiliary skin-friction field and its applicability to global skin-friction diagnostics are discussed.